2016
DOI: 10.1371/journal.pone.0167295
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Environmental Impact of Rice Blast Pathogen (Magnaporthe oryzae) Alleviation in the United States

Abstract: Rice blast (Magnaporthe oryzae) is a key concern in combating global food insecurity given the disease is responsible for approximately 30% of rice production losses globally—the equivalent of feeding 60 million people. These losses increase the global rice price and reduce consumer welfare and food security. Rice is the staple crop for more than half the world’s population so any reduction in rice blast would have substantial beneficial effects on consumer livelihoods. In 2012, researchers in the US began ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(134 citation statements)
references
References 19 publications
1
113
0
2
Order By: Relevance
“…In recent years, improved chemical methods like use of organomercuric, organophosphorus and copper fungicides, antibiotics like Kasugamycin and Blasticidin S, site specific and systemic fungicides including melanin biosynthesis suppresser and plant activators and leaf extracts are utilized successfully for blast management [22]. Thus the researcher has to pay emphasis in producing blast-resistant rice with lower ecotoxicity, eutrophication, carcinogenics and acidification impact [4]. Several scientific study have identified plant species with more than 2400 bioactive compounds having insecticidal and anti-pathogenic properties, commonly referred as 'green pesticides', which are more compatible with environmental components compared to synthetic pesticides [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, improved chemical methods like use of organomercuric, organophosphorus and copper fungicides, antibiotics like Kasugamycin and Blasticidin S, site specific and systemic fungicides including melanin biosynthesis suppresser and plant activators and leaf extracts are utilized successfully for blast management [22]. Thus the researcher has to pay emphasis in producing blast-resistant rice with lower ecotoxicity, eutrophication, carcinogenics and acidification impact [4]. Several scientific study have identified plant species with more than 2400 bioactive compounds having insecticidal and anti-pathogenic properties, commonly referred as 'green pesticides', which are more compatible with environmental components compared to synthetic pesticides [23].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogen, a holomorph of a complex of heterothallic Ascomycetes, is most damaging of rice diseases [3]. It causes high yield loss about 30% globally [4], and thus major threat to global food security [5]. In India, rice blast is a major production constraint in irrigated ecosystem [6] and under severe epiphytic conditions may result a loss of 70-90% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Rice blast caused by Magnaporthe oryzae, which is the most economically serious disease in rice, is responsible for annual losses of more than 30% [172]. This fungal pathogen has a hemibiotrophic life style and infects its host at any developmental stage, causing damage to multiple tissues: Leaf, stem, node, or panicle [173].…”
Section: Rice Blast Diseasementioning
confidence: 99%
“…In the United States, planting high-production rice varieties that are susceptible to SB, resulted in up to 50% yield losses 3 , in a severe breakout season. As a result, about 72% of the rice planting area in the United States is sprayed with fungicide that incurs unsustainable economic cost to the farmers 6 . The spraying may also pose severe ecological constraints on animals and microbiome that co-inhabit and/or frequently visit rice farms and fresh water bodies.…”
Section: Introductionmentioning
confidence: 99%